Differences in content of beet root and beet root juice, and it’s suitable to develop functional foods from animal sources - Nagy, Anikó; Jávor, András; Takácsné Hájos, Mária; Borbélyné Varga, Mária; Soltész, Pál; Csiki, Zoltán (Acta Agraria Debreceniensis, 2015)
In Western medicine is beginning to increasingly focus on the key role of healthy nutrition and lifestyle in preventing certain diseases. Therefore, it is important to emphasize the importance of primary prevention in our country, and to promote it; not only the health care team work, but broaden the recommended foods, which have benefit for human health as well.Polyphenols are antioxidants, which are easily consumable with diet, however, food processing can influence the level of them.In our study, nutritional assessment was made of raw beet root and a juice, made from this beet root. We investigated in which special diet referenced to eat this foods and whether this is suitable to develop functional foods from animal sources as a row material.